Genetics of the Deli-Avros Breeding Populatins of the Oil Palm (Elaeis Gulneensis Jacq.) - Bilal, Musa (2004)
This study was conducted to assess the phenotypic and genetic properties of two Deli-AVROS dura x pisifera breeding populations, which have gone througL -1es of selection. The specific objectives for this study were: (i) to estimate phenotypic and genetic variances, additive and dominance genes effects and heritabilities (broad-sense and narrow-sense) for 20 traits measured in these two populations, (ii) to estimate phenotypic and genetic coefficients of variation for the traits concerned, (iii) to estimate phenotypic correlations among the traits concerned, and (iv) to estimate the general combining ability (GCA) of the male parents involved for the traits concerned. The populations consisted of 33 dura x pisifera crosses, generated from controlled pollinations between female (dura) and male (pisifera) parents, following the North Carolina Mating Design I (NCM I). Population 1 with 15 crosses (5 males and 15 females) and Population 2 with 18 crosses (6 males and 18 females ) had been grown in 1995, at two separate locations (Sg.Buloh and Nova Scotia estates, respectively) on coastal soils (Typic Tropaquept), in Consolidated Plantations Berhad, in . . 11 Peninsular Malaysia. These crosses had been previously planted in a Randomised Complete Block Design with three replications, with 12 palms (4x3) per plot, spaced at 8.8 metres in equilateral triangular pattern. Data on yield (fresh h i t bunch weight and bunch number), bunch and fruit components, vegetative traits and physiological traits were collected from these palms from January 2000 to December 2000. Variability analysis revealed low phenotypic coefficients of variation (pcv) and low genetic coefficients of variation (gcv) for most of the traits measured in these two Deli-AVROS populations. Fresh fruit bunch yieldlpalm, bunch numberlpalm, average bunch weight, % fruit/bunch, % oilhunch, % mesocarplfruit, % oil/mesocarp, vegetative traits and physiological traits clearly showed low pcv and gcv values. However, % kernellbunch, % kernellfruit and % shelllfruit still maintained their moderate pcv and gcv values in both populations. Relatively high dominance variances compared to their corresponding additive variances were recorded for fresh fi.uit bunch yieldJpalm, average bunch weight, % oil/bunch, fruit weight, and most vegetative and physiological traits in these two Deli-AVROS populations. However, higher additive variances compared to their dominance counterparts were shown for bunch numberlpalm and % mesocarplfruit in both populations. Broad-sense heritability estimates for most of the traits measured in these populations ranged from moderate to high, indicating that these traits were largely under genetic control and to a smaller extent influenced by the environmental factors. Narrow-sense heritability estimates revealed that bunch numberlpalm, % *. . 111 rnesocarplfruit and leaf area index were heritable, compared to traits viz. fresh fruit bunch, trunk girth and bunch dry matter which were less heritable in both populations. Correlation analysis revealed that fresh fruit bunch yieldpalm was positively correlated with bunch nurnberlpalm and average bunch weight in both populations. Among the bunch and fruit components, % fruithunch was positively correlated with % oilhunch and % kernelhunch, while % oilhunch was significantly correlated with % mesocarplfruit and % oil/mesocarp in both populations. Among the vegetative traits, petiole cross section was positively correlated with rachis length in both populations. This study has identified AVROS pisifera parents with good general combining ability (GCA) for fresh fruit bunch yieldpalm, % oillbunch, % kernelhunch and bunch index. The two Deli-AVROS breeding populations had low phenotypic and genetic variability for most of the traits measured. An effort has to be taken to broaden their genetic variability by introgression of genes from other germplasm sources.